2016
DOI: 10.2106/jbjs.cc.15.00273
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Rupture of Posterior Tibial Tendon Following Closed Supination-Adduction Ankle Fracture

Abstract: At 1 year of follow-up, the ankle had good union and function of the tendon was restored. Posterior tibial tendon ruptures, although rare, should be suspected in cases of closed ankle fracture, irrespective of the mechanism of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A PTT rupture associated with a closed tibial fracture is extremely rare. The only 2 cases present in the literature are reported in the articles by Jarvis and Cannada (24) in 2012 (complete lesion of nonrepairable PTT with direct suture associated with an extra-articular fracture of the distal tibia) and by Korovessis et al (25) in 1991 (complete lesion of the PTT and of the flexor digitorum longus tendon associated with extra-articular fracture in the distal third of the tibia).…”
Section: Discussionmentioning
confidence: 99%
“…A PTT rupture associated with a closed tibial fracture is extremely rare. The only 2 cases present in the literature are reported in the articles by Jarvis and Cannada (24) in 2012 (complete lesion of nonrepairable PTT with direct suture associated with an extra-articular fracture of the distal tibia) and by Korovessis et al (25) in 1991 (complete lesion of the PTT and of the flexor digitorum longus tendon associated with extra-articular fracture in the distal third of the tibia).…”
Section: Discussionmentioning
confidence: 99%
“… Traumatic rupture of the posterior tibial tendon occurring during a closed fracture of the ankle: report of a case. [ 22 ] Pan Afr Med J 2015 1 Krishna S.V., Pilar A., Pai S.N., Issac T. Traumatic Rupture of Posterior Tibial Tendon Following Closed Supination-Adduction Ankle Fracture: A Case Report [ 23 ] JBJS Case Connect 2016 1 Formica, M.; Santolini, F.; Alessio-Mazzola, M.; Repetto, I.; Andretta, A.; Stella, M. Closed medial malleolar multifragment fracture with a posterior tibialis tendon rupture: a case report and review of the literature [ 24 ] J Foot Ankle Surg 2016 1 Park, J. Partial rupture of the tibialis posterior tendon associated with a closed medial malleolar fracture (A case report) [ 25 ] Journal of the American Podiatric Medical Association 2016 1 Jasqui-Remba S, Rodriguez-Corlay RE.…”
Section: Tablementioning
confidence: 99%
“…Some studies have reported on the rupture in association with fractures of the medial malleolus. [1][2][3] However, rupture associated with overuse in athletes without any fractures is uncommon. 4,5 The posterior tibial tendon is the largest tendon located in the medial ankle.…”
mentioning
confidence: 99%